Little women - Alcott, Louisa May 1832-1888 (New York Puffin Books, 2004)
Chronicles the joys and sorrows of the four March sisters as they grow into young ladies in nineteenth-century New England
Keywords: March family (fictitious characters) -- Juvenile fiction; Family -- New England -- Juvenile fiction; Sisters -- New England -- Juvenile fiction; Family life -- New England -- Fiction; Sisters -- Fiction; Domestic fiction